2010
DOI: 10.1016/j.mcn.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte secreted proteins selectively increase hippocampal GABAergic axon length, branching, and synaptogenesis

Abstract: Astrocytes modulate the formation and function of glutamatergic synapses in the CNS, but whether astrocytes modulate GABAergic synaptogenesis is unknown. We demonstrate that media conditioned by astrocytes, but not other cells, enhanced GABAergic but not glutamatergic axon length and branching, and increased the number and density of presynaptically active GABAergic synapses in dissociated hippocampal cultures. Candidate mechanisms and factors, such as activity, neurotrophins, and cholesterol were excluded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 43 publications
(60 reference statements)
6
107
1
1
Order By: Relevance
“…Conditioned media from wt astrocytes, but not from HD astrocytes, rescued the neuritic defect, suggesting that cholesterol dysfunction in glial cells may contribute to neuritic morphology defects, thereby compromising neuron function. Although several glialderived factors may contribute to neurite outgrowth in cultured neurons, 38 we demonstrated a direct link between glial cholesterol and neurite outgrowth in HD neurons. First, we showed that cholesterol administration rescued neuritic defects in HD neurons during early stages of differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…Conditioned media from wt astrocytes, but not from HD astrocytes, rescued the neuritic defect, suggesting that cholesterol dysfunction in glial cells may contribute to neuritic morphology defects, thereby compromising neuron function. Although several glialderived factors may contribute to neurite outgrowth in cultured neurons, 38 we demonstrated a direct link between glial cholesterol and neurite outgrowth in HD neurons. First, we showed that cholesterol administration rescued neuritic defects in HD neurons during early stages of differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…TSP-induced synapses in culture are ultrastructurally normal and presynaptically active, but lack postsynaptic activity (Christopherson et al 2005;Eroglu et al 2009). TSPs do not promote inhibitory GABAergic synaptogenesis (Hughes et al 2010). Glutamatergic synapatogenic activity is mediated by interaction of the EGF-like domains of TSPs with the vWF_A domain of a2d-1, a ubiquitously expressed, nonessential subunit of L-type calcium channel that is the target of the drug gabapentin (Eroglu et al 2009).…”
Section: Neuronal Cellsmentioning
confidence: 99%
“…Above all, we describe a serum -free culturing method for long -term neuronal cultures with preserved functionality and connectivity, reminiscent of that seen in the intact tissue. The three culturing protocols that we compared were: I-FBS based medium (traditionally used in our lab 26 and by other research groups 17,27,28 ; II-Neurobasal/B27 medium as described in Beaudoin 7 ; III-our serum -free ACM medium. The exact composition for all the three growing media is reported in the Methods section and the conditions are referred to as FBS, B27 and ACM, respectively.…”
Section: Introduction *Manuscript (With Page Numbers) Click Here To Dmentioning
confidence: 99%